Subacute cognitive deterioration with high serum anti‐thyroid peroxidase antibodies: two cases and a plea for pragmatism. Issue 3 (17th September 2013) - Segers, Kurt; Braconnier, Philippe; Corazza, Francis; Divano, Luisa; Mabrouk, Asmaa; Robberecht, Jean; Surquin, Murielle
Abstract Autoimmune encephalopathy is a rare but potentially reversible cause of cognitive deterioration and neuropsychiatric disturbances. We describe two older female patients with subacute cognitive decline and marked neuropsychiatric disturbances in the presence of high serum anti‐thyroid peroxidase antibodies and with normal dosage of free thyroxine 4. One patient recovered almost completely after oral corticotherapy. Differential diagnosis and the role of biomarkers, in particular, are discussed. We support a pragmatic approach involving a short empirical therapeutic trial with intravenous or oral corticoids; this should be considered in all patients with subacute encephalopathy and with laboratory arguments for an underlying autoimmune aetiology.